God's battalions: the case for the Crusades - Stark, Rodney (HarperOne, 2010)
In God's Battalions, award-winning author Rodney Stark takes on the long-held view that the Crusades were the first round of European colonialism, conducted for land, loot, and converts by barbarian Christians who victimized the cultivated Muslims. Instead, Stark argues that the Crusades were the first military response to Muslim terrorist aggession